THE EFFECT OF CUTTING SPEED AND FEED RATE ON THE DRILLED HOLES QUALITY OF TITANIUM ALLOYS, TI-6AL-4V - GHANI, FATIN SYAMIMI (IRC, 2017)
Titanium alloy, Ti-6Al-4V is gaining popularity in aerospace, automotive and biomedical industries due to the superior properties exhibition like high strength to weight ratio, good resistance corrosion and fatigue resistance. Unfortunately, it leads to the difficulties in machining operation of Ti-6Al-4V. The surface roughness, final diameter, burrs and chips formation are observed and study as the criteria of the indication for the drilling process. In this paper, study is conducted in varying cutting parameters; cutting speed and feed rate in drilling operation. The aim is to come out with the most optimum cutting parameters condition for the drilling of titanium alloy using High Speed Steel (HSS). Presentation of the conclusion is by the end of this paper which is focused on the criteria to be met and future work required to improve the drilling of titanium alloy, Ti-6Al-4V.